Defect-dipole defined nanoscale ferroelectric polar-orders induced in Barium Zirconate. (15th March 2017) - Dutta, Moumita; Ding, Ying; Chen, Jianghua; Chen, Chonglin; Bhalla, Amar; Guo, Ruyan
Abstract: Nanoscale ferroelectric behaviour has been investigated in epitaxial BaZrO3 thin films grown in an oxygen deficient environment. Though centrosymmetric in nature, prominent ferroelectric polar states were observed via Piezo Force Microscopy (PFM), with polarization switching achieved when oppositely poled. Absence of intrinsic polar directions annul the conventional root causes for ferroelectricity like structural asymmetry and strain, rather attributes the nanoscale polar orders observed, to defect dipoles originated from oxygen vacancies introduced during the film growth. Electrostatic Force Microscopy (EFM) exhibiting inhomogeneous distribution of surface potential confirms the accumulation of oxygen vacancies contributing towards the measured polarizations. Graphical abstract: